Jatrorrhizine inhibits mammary carcinoma cells by targeting TNIK mediated Wnt/β-catenin signalling and epithelial-mesenchymal transition (EMT) - Yanfang, Sun; Wink, Michael (Phytomedicine, 2019)
Background - Traf2 and Nck interacting serine protein kinase (TNIK) is a tumour target protein which its high expression is closely related to the occurrence and development of mammary carcinoma cells. Molecular docking revealed that jatrorrhizine, a protoberberine alkaloid, exhibits good binding affinity and interaction with TNIK. However, the underlying mechanisms of jatrorrhizine targeting TNIK inhibits the proliferation and metastasis of breast cancer cells remain unclear. - Methods - To figure out the mechanisms in vitro and in vivo, the CRISPR/Cas9 technology was used to knockout TNIK gene and detected qualitatively by immunofluorescence and immunoblotting assay. The MTT cell viability assay for cytotoxicity test, the apoptosis were detected by flow cytometry, the migration and invasion were evaluated by colony formation, wound healing assay and cell invasion assay, respectively. Anticancer effects were further corroborated by 4T1/Luc homograft tumour model. - Results - The results showed that targeted knockout of TNIK that attenuated Wnt/β-catenin signalling and epithelial-mesenchymal transition (EMT) expression, the effects were potentiated by the addition of jatrorrhizine. Moreover, jatrorrhizine distinctly inhibited the proliferation of MDA-MB-231, MCF-7 and 4T1 cells with IC50 values of 11.08 ± 1.19μM, 17.11 ± 4.54μM and 22.14 ± 2.87μM, induced mitochondrial dysfunction and early apoptosis involving mitochondrial apoptotic pathway. These results were further corroborated by the 4T1 tumour-bearing mice, which showed that jatrorrhizine significantly suppressed the proliferation and metastasis of mammary carcinoma cells without obvious toxicity. - Conclusion - These findings provide an overall perspective that jatrorrhizine potentially restrains TNIK regulating Wnt/β-catenin signalling and EMT expression for mammary cancer targeted therapy.
Available online 3 July 2019
Gesehen am 13.01.2020